Le bien-être des animaux d'élevage Améliorer le bien-être animal - Mounier, Luc (éditions Quae, 2022)
Following on from the 'Understanding' and 'Assessing' booklets, this booklet presents ways to improve farm animal welfare, focusing on the physical and social environment of animals, the human-animal relationship, pain management, and humane transport and slaughter. Certain levers for improvement are particularly highlighted, such as the creation of positive relationships based on a better understanding of animals, the integrated management of their health and the promotion of solutions to eliminate, replace or relieve painful practices. The implementation of actions must of course be adapted to each farm, and also respect the well-being of the farmer. This approach is part of the "one welfare" concept, where the benefits for the animal, for humans and for the environment are closely linked. This book is intended for students and professionals in the agricultural and veterinary sectors, as well as for any citizen interested in the welfare of farm animals.